QUALITY OF ADMINISTRATIVE SERVICES THROUGH THE E-PAK LADI PROGRAM IN CANGKRINGMALANG VILLAGE, PASURUAN REGENCY - Suaedi, Ach; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective This study aims to determine the quality of administrative services through the E-Pak Ladi program in Cangkringmalang Village, Pasuruan Regency. The research focuses on evaluating five dimensions of public service quality: tangibles, reliability, responsiveness, assurance, and empathy, in the context of implementing digital administrative services at the village level.. Method: The method used in this study was descriptive with a qualitative approach. Data collection techniques included direct observation, in-depth interviews with the community and village officials, and documentation of the implementation of the E-Pak Ladi program. This study aims to comprehensively describe the actual conditions on the ground and explore various obstacles and successes in service implementation. Results The results of the study indicate that the quality of service through the E-Pak Ladi program varies across dimensions. The tangible dimension declined because the comfort indicator for the location had not been met, even though other physical aspects were available. The reliability dimension met community expectations and the service was considered reliable. Responsiveness was considered quite good, especially in responding to citizen complaints and grievances. In the assurance dimension, the community was satisfied because the service was provided with a clear time guarantee. Meanwhile, the empathy dimension performed well with intensive communication between village officials and the community.. Novelty: The novelty of this research lies in its specific focus on the implementation of digital population administration services at the village level, a practice rarely studied in depth. Furthermore, using the latest local data from 2022–2024, this study successfully identified practical challenges and applicable solutions that can be implemented by village governments. This research is expected to serve as a reference for developing digital public services in other rural areas in Indonesia..